Needs Analysis of the Biology Interactive Module Based on Bengkulu Local Wisdom - Syahfitri, Jayanti; Muntahanah, Muntahanah (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Packaging local wisdom in learning materials will make it easier to deliver the material, and students can connect their knowledge with the real situations they face. This research aims to analyze student needs for interactive digital modules based on Bengkulu local wisdom. This research type is the Research and Development (R D) using the ADDIE model, but this research is limited to the Analyze stage. Data was collected by interviewing several biology subject teachers and giving questionnaires via google form to 96 students. The teachers and students involved were taken from several high schools in Bengkulu, Indonesia. The student needs analysis questionnaire includes seven indicators, and then the data obtained is analyzed through the qualitative description. The results show that: 1) the biology learning curriculum used in high school has not specifically been integrated with local wisdom, 2) the learning resources that have been used are textbooks, worksheets, e-books, environment, videos, and internet media, 3) as many as 52.1% of students admitted that they did not know and used interactive modules, 66.7% of students did not understand local wisdom in Bengkulu, and as many as 95.8% of students stated the need for interactive modules to support biology learning. Thus, it can be concluded that it is necessary to develop an interactive module based on Bengkulu's local wisdom as a supporting learning resource in learning biology.